“Who The F*** Are Arctic Monkeys?”: representations of the British youth in the first decade of the 20th century - Carvalho, Icaro; Dariva, Bruno Amaral (Scriptorium, 2020)
The present work aims to study the way the British youth from the early 2000s is portrayed through lyrics of the debut album by the English band Arctic Monkeys. On January 23 in the year of 2006, when a group formed by four young men, who were 19 years old, released an album called Whatever People Say I Am, That’s What I’m Not, the CD surprisingly became the fastest selling debut album in the British music history. The choice of this album as study corpus is based not only on account of the commercial success mentioned above, but also on the compositions’ precise and literary portraying of current aspects of the British youth in the first decade of the millenium. By analysing the excerpts, which portray the routine of a generation, the work aims to contribute to a more informed understanding of the social habits that made this atmosphere possible. O presente trabalho almeja estudar a forma como a juventude britânica do início dos anos 2000 é apresentada em algumas letras do álbum de estreia da banda inglesa Arctic Monkeys. Em 23 de janeiro de 2006, quando um grupo de quatro rapazes de dezenove anos lançou o álbum chamado Whatever People Say I Am, That’s What I’m Not, o disco surpreendentemente tornou-se o álbum de estreia mais vendido na história da música britânica. A escolha deste álbum como corpus de estudo não levou em conta apenas o sucesso comercial referido, mas também o fato de as composições representarem, de forma muito precisa – e também literária – aspectos recorrentes na vida da juventude inglesa na primeira década do milênio. Utilizando as composições, que refletem hábitos de uma geração de jovens ingleses, pretende-se melhor compreender a sociedade e os costumes que a orbitavam e faziam com que essa atmosfera específica existisse.